Ambient Lithium–SO2 Batteries with Ionic Liquids as Electrolytes1. (20th January 2014) - Xing, Huabin; Liao, Chen; Yang, Qiwei; Veith, Gabriel M.; Guo, Bingkun; Sun, Xiao‐Guang; Ren, Qilong; Hu, Yong‐Sheng; Dai, Sheng
Abstract Li‐SO2 batteries have a high energy density but bear serious safety problems that are associated with pressurized SO2 and flammable solvents in the system. Herein, a novel ambient Li‐SO2 battery was developed through the introduction of ionic liquid (IL) electrolytes with tailored basicities to solvate SO2 by reversible chemical absorption. By tuning the interactions of ILs with SO2, a high energy density and good discharge performance with operating voltages above 2.8 V were obtained. This strategy based on reversible chemical absorption of SO2 in IL electrolytes enables the development of the next generation of ambient Li‐SO2 batteries.